Effects of TLR7 Polymorphisms on the Susceptibility and Progression of HIV-1 Infection in Chinese MSM Population - Zhang, Tong; Zhu, Junping; Su, Bin; Cao, Lina; Li, Zhen; Wei, Huanhuan; Huang, Xiaojie; Zheng, Kai; Li, Aixin; Chen, Ning; Liu, Lifeng; Xia, Wei; et al. (Frontiers in Immunology, 2020)
Toll-like receptor (TLR) 7 plays a key role in innate and adaptive immunity for HIV-1 infection. We evaluated the effect of TLR7 polymorphisms on disease susceptibility and progression of HIV-1 infection in Chinese MSM (men who have sex with men). Blood samples were taken from 270 patients with laboratory confirmed HIV infection, 196 male controls were tested, and three TLR7 intronic polymorphisms (rs179010-C > T, X:12884766; rs2074109-T > C, X:12885330 and rs179009-A > G, X:12885361) were analyzed by PCR-based sequencing. The frequency of TLR7 rs179010 T allele was significantly lower in MSM patients than in controls (P=0.039). The haplotype TTA was associated with a decreased susceptibility to HIV-1 infection (P=0.013), especially to acute HIV-1 infection (AHI) (P=0.002), but not to chronic HIV-1 infection (CHI). Furthermore, the haplotype TTA is linked to slow disease progression in AHI patients (P=0.000) and a lower viral load (P=0.042). In contrast, TLR7 rs179009 allele A contributed to a higher set point in AHI patients with rapid progression, and the frequency of rs179009 minor allele G was over-presented in CHI patients. Our study indicates that TLR7 rs179010 minor allele T and haplotype TTA play a protective role in susceptibility to and progression of an acute HIV-1 infection by inhibiting viral load, while TLR7 rs179009 minor allele G and haplotype CTG serve as a risk factor in the chronic stage of HIV-1 infection. This finding supports a role for genetic variations of TLR7 in susceptibility and disease progression of an HIV-1 infection.